The asymmetric synthesis of beta-haloaryl-beta-amino acid derivatives - Bull, S; Davies, S; Delgado-Ballester, S; Fenton, G; Kelly, P; Smith, A (2000)
Lithium N-benzyl-N-α-methyl-4-methoxybenzylamide is employed as a homochiral ammonia equivalent for the asymmetric synthesis of β-haloaryl-β-amino acid derivatives using a conjugate addition/oxidative deprotection strategy.